The Relationship Between Nurses’ Caring Behavior and Patient Trust in Primary Health Care Settings - Sofia Hanifa; Layla Layla; Nadia Salma (International Journal on Health and Medical Sciences, 2025)
Patient trust is a fundamental element of effective primary health care services and is closely influenced by the quality of nurse patient interactions. Nurses, as frontline health professionals, play a key role in building trust through caring behaviors such as empathy, respect, and effective communication. This study aimed to examine the influence of nurses’ caring approach on patient trust in primary health care services. A quantitative correlational design was used involving patients receiving nursing services in primary health care facilities. Data were collected using structured questionnaires measuring nurses’ caring approach and patient trust, and analyzed using correlation and regression techniques. The findings showed a significant positive relationship between nurses’ caring approach and patient trust. Empathy and communication were identified as the strongest caring dimensions influencing patient trust. Nurses’ caring behaviors significantly contribute to the development of patient trust in primary health care services. Strengthening caring-based nursing practices is essential to enhance patient-centered care and service quality.